Art-Map: concept of moving curatorial project and its practical realization in Aveiro - Ziganshina, Madina (2015)
In this dissertation, I present the results of a project which aim was to find out and try an effective model of independent curatorial project executable in small and medium cities in Portugal. The concept of Moving Curatorial Project ARTMAP is a result of theoretical research and reflection about municipal exhibition spaces and possibility of presentation of the contemporary art in these spaces. To test if this curatorial project is realizable and if there are conditions to continue it, a first trial was implemented in Aveiro. A curated international exhibition, entitled “A Poética do Visual" occupied two municipal and two private gallery spaces and brought together 111 artists from 25 different countries. The art event was carried out in collaboration with the Municipality of Aveiro and the University of Aveiro, and involved several private cultural spaces in the city. This first experience showed that there are all conditions for the presentation of contemporary art in small and medium size locations in Portugal, and for this project to be replicated in other regions of the country.